Platinum(ii) binuclear complexes: molecular structures, photophysical properties, and applications. Issue 20 (7th May 2019) - Chaaban, Maya; Zhou, Chenkun; Lin, Haoran; Chyi, Brandon; Ma, Biwu
Abstract : Platinum(ii ) binuclear complexes with two metal centers facing each other are reviewed based on their molecular structures, photophysical properties, and applications in light emitting and sensing devices. Abstract : Platinum(ii ) binuclear complexes containing two platinum centers bridged by different types of ligands have received great research attention for their unique properties and potential applications in a variety of areas. The properties of these binuclear Pt(ii ) complexes, which could be significantly different from those of their mononuclear counterparts, are highly tunable by modifying their cyclometallating ligands and bridging ligands, as well as their structural configurations. The photophysical properties of these complexes involving a wide range of spectroscopic phenomena make them a very interesting class of materials to be spectroscopically studied. Applications of platinum(ii ) binuclear complexes have been explored in several areas, ranging from light emitting diodes, to sensors and photocatalysis. In this review, the molecular structures, photophysical properties, and applications of a variety of platinum(ii ) binuclear complexes are discussed. We intend to shed some light on the recent progress in this field and give a future outlook.